2022
DOI: 10.3390/brainsci12020253
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Fitting Optimization Using Evolutionary Algorithm in Cochlear Implant Users with Bimodal Binaural Hearing

Abstract: Optimizing hearing in patients with a unilateral cochlear implant (CI) and contralateral acoustic hearing is a challenge. Evolutionary algorithms (EA) can explore a large set of potential solutions in a stochastic manner to approach the optimum of a minimization problem. The objective of this study was to develop and evaluate an EA-based protocol to modify the default frequency settings of a MAP (fMAP) of the CI in patients with bimodal hearing. Methods: This monocentric prospective study included 27 adult CI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…Recently, a pilot study was performed in which implanted subjects showed better results on speech discrimination tests with an anatomically based FAT compared to their routine clinical settings ( Di Maro et al, 2022 ). Other strategies to improve CI frequency distributions have also been evaluated, such as evolutionary algorithms and smartphone applications which enable FAT self-adjustment by patients ( Fu et al, 2002 ; Jethanamest et al, 2017 ; Saadoun et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a pilot study was performed in which implanted subjects showed better results on speech discrimination tests with an anatomically based FAT compared to their routine clinical settings ( Di Maro et al, 2022 ). Other strategies to improve CI frequency distributions have also been evaluated, such as evolutionary algorithms and smartphone applications which enable FAT self-adjustment by patients ( Fu et al, 2002 ; Jethanamest et al, 2017 ; Saadoun et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Acoustic models that drive cochlear implants are constrained by the number and tuning of channels, temporal resolution, and topographical discrepancy between the frequency information provided by the electrode and the natural tuning of the cochlea. Interactive genetic algorithms and evolutionary algorithms can support optimization of acoustic models at a more efficient rate of convergence than natural adaptation [ 259 , 260 ]. Models simulating listener errors can also be used to inform development of such algorithms [ 258 ].…”
Section: Models For Neurorehabilitationmentioning
confidence: 99%
“…Also the usability of evolutionary algorithms to optimize the frequency fitting is currently investigated and shows promising results concerning speech outcome and sound quality, whereas specific binaural benefits are yet unknown ( Saadoun et al, 2022 ).…”
Section: Mismatch Compensation and Side Effectsmentioning
confidence: 99%